2021
DOI: 10.1186/s12894-021-00783-x
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Sperm parameters and anti-Müllerian hormone remain stable with Helicobacter pylori infection: a cross-sectional study

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Secretion peaks during foetal life until puberty and declines to low levels after adulthood. It is mainly involved in the regulation of cell differentiation and accelerates degenerate mullerian in male embryos [12][13][14]. Data have shown that AMH can play a regulatory function during sperm generation and promote sperm formation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Secretion peaks during foetal life until puberty and declines to low levels after adulthood. It is mainly involved in the regulation of cell differentiation and accelerates degenerate mullerian in male embryos [12][13][14]. Data have shown that AMH can play a regulatory function during sperm generation and promote sperm formation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%